(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
PyKaldi is much more than a set of Kaldi library bindings. It offers best level of compatibility for OpenFst classes with the tool “Kaldi” to make dealing with Kaldi easier for Python users. PyKaldi is wrapper most probably written in a language known as “Python” for the widely used Kaldi SR toolkit that is free and open-source. PyKaldi isn’t only a set of Python bindings for Kaldi libraries. It’s a Python-based coding that lets programmers or developers interact with OpenFst types or Kaldi in real time. NumPy arrays are strongly integrated with both of the tools discussed. PyKaldi, we hope, will substantially improve the user experience and make integrating Kaldi into Python processes much easier. PyKaldi has a lot of documentation and testing. It supports Python 3 and also the previous version 2, and is distributed under the Apache License version 2.0. The fact that Kaldi has been so efficacious should not arise as any wonder. The features related to licence, rich documentation, tried methods for developing cutting-edge systems, a big number of international contributors, a devoted set of maintainers, and, perhaps most significantly, a well-designed codebase that is simple to comprehend, alter, and expand.